Efeitos do fogo sobre assembleias de aves de cerrado - Reis, Matheus Gonçalves dos (2015)
Fire is an ecological factor which seasonally affects fire-prone ecosystems, such as grasslands and open savannas of the Cerrado, and changes some patterns of the biota. This study aimed to investigate the influence of fire on birds that directly use food resources in grasslands of the Serra da Canastra National Park. From December 2012 to January 2015, sampling efforts were carried out in areas burned by wildfires, prescribed burnings (environmental management strategy) and in areas with no influence of fire, in order to record birds in foraging activities, their diet and the use of microhabitat for foraging. The 92 bird species recorded throughout the study exhibited specific results of the occurrence, abundance and response to fire. Considering all birds, the wildfires exerted a deeper and longer (3 - 4 months) influence on assemblage structure, than the prescribed burnings (2 - 3 months). The fire effects on some species of birds were observed in the proportion of food categories consumed, in the diversity of diet items and the microhabitats selected for foraging. The fire response models for birds of prey that occupy the top of the food chain in grasslands indicated a more intense use of food resources in the first post-fire months. Environmental management towards the conservation of grassland ecosystems depends on understanding the effects of recurrent disturbances on native species.